A giant pseudoaneurysm of coronary artery in a young patient with Behçet's disease. Issue 11 (29th October 2017) - Pu, Lihong; Li, Rongjuan; Xie, Jinjie; Liu, Guowen; Yang, Ya
Abstract : As an uncommon multisystem inflammatory disease, Behçet's syndrome is characterized by mouth and genital ulcers, skin lesions, and eye inflammation, which may also affect joints, blood vessels, central nervous system, or digestive tract. However, the inflammation of coronary artery is relatively rare. We thereby reported a young male of Behçet's syndrome presenting left anterior descending artery pseudoaneurysm with myocardial infarction. Surgical resection was performed with coronary bypass grafting.